Revisions, and Quiddities - Armstrong, David
I used to think of the connection between a particular and a universal that it instantiates as a contingent one. Now I think that this is not quite right. This revision, as I now see it, is not a very large one. I still think that the states of affairs (Russell’s facts in his great Lectures on Logical Atomism) that unite particulars and universals are contingent beings. But the connection within states of affairs is, in a certain way, necessary.